The possibility of access to the kidneys from posterior axillary line in supine position for percutaneous nephrolithotomy - Tabibi, Ali; Kashi, Amir Hossein; Mirjalili, Seyed Ali Mohammad; Mahmoudnejad, Nastaran; Kashani, Paria; Salavatipour, Babak; Soltani, Mohammad Hossein (Novelty in Biomedicine, 2013)
Please cite this article as: Tabibi A, Kashi AH, Mirjalili SAM, Mahmoudnejad N, Kashani P, Salavatipour B, Soltani MH. The possibility of access to the kidneys from posterior axillary line in supine position for percutaneous nephrolithotomy. Novel Biomed 2013;1(2):43-47. Objectives: To evaluate the possibility of access to the kidneys from posterior axillary line (PAL) in supine position for percutaneous nephrolithotomy. Materials and Methods: 102 consecutive patients who were candidated for abdominal CT scan, enrolled in this study. In cases of impossible access, the point on the posterior surface of body which permitted safe access was determined and the percent of movement toward body midline (relative to PAL) was calculated (M.PER). Results: Percutaneous access was simulated from upper and middle calyces of the kidney in 13% and 75% of cases, respectively. Access to the lower region was possible in 90% of right and 79% of left lower calyces, respectively (p=0.03). In cases with impossible access from PAL, the M.PER for a safe access was 46-47% for upper region and 34- 38% for middle and lower calyces of the kidney (P = 0.0001). Conclusions: Access to upper calyces from PAL was limited in some cases regarding to the presence of solid organs. Presence of colon made access impossible in the lower right and left calyces in about 10% and 20% of cases, respectively. In upper region, more deviation toward midline was necessary to establish a safe access compared with middle and lower calyces.